STRATEGI PEMBELAJARAN ALAT MUSIK BAMBU PADA KEGIATAN EKSTRAKURIKULER DI SEKOLAH DASAR NEGERI 94 LALONG KABUPATEN LUWU SULAWESI SELATAN - Ningsih, Dwi Utami (Program Studi Pendidikan Musik, 2022)
This study aims to describe and inform the bamboo musical instrument learning strategy for extracurricular activities in the State Elementary School 94 Lalong. The research method used is descriptive qualitative methods. The research took place in SDN 94 Lalong and in Lalong Village houses, Walenrang, Luwu Regency, South Sulawesi, before and after the pandemic, started from October 2019 until June 2021. Data is collected through observation, interview and literature study, and triangulation for data validity. The result of this study is showed that bamboo musical instrument learning strategy for extracurricular activities in SDN 94 Lalong Luwu Regency South Sulawesi, used Participative Teaching and Learning strategy is learning that involved coach as the center and students as learners from early planning, implementation, and evaluation. Learning methods used are demonstration, question and answer, drill, Team Teaching, and Kodaly methods. Other than that, with the existence of bamboo musical instrument extracurricular activities in SDN 94 Lalong, Luwu Regency, bamboo musical art can be elevated and become a motivation for Luwu community and other regions to keep on preserving bamboo musical art from Luwu Regency, South Sulawesi.